2021
DOI: 10.1038/s41467-021-22154-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of mosaic structure in strongly supercooled molecular liquids

Abstract: When a liquid is cooled to produce a glass its dynamics, dominated by the structural relaxation, become very slow, and at the glass-transition temperature Tg its characteristic relaxation time is about 100 s. At slightly elevated temperatures (~1.2 Tg) however, a second process known as the Johari-Goldstein relaxation, βJG, decouples from the structural one and remains much faster than it down to Tg. While it is known that the βJG-process is strongly coupled to the structural relaxation, its dedicated role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Similar sudden and hardly predictable re-arrangements have been found in simulations of active Ornstein-Uhlenberg particles [55], sheared granular media [56] and in epithelial tissues [34]. Interestingly, the string-like cooperative motion of particles in a closeto glassy state were observed in super-cooled liquids [57,58], simulations of Lennart-Jones mixtures [59] and granular beads [60].…”
Section: Dynamic Heterogeneity Due To the Co-existence Of Locally Ent...supporting
confidence: 65%
“…Similar sudden and hardly predictable re-arrangements have been found in simulations of active Ornstein-Uhlenberg particles [55], sheared granular media [56] and in epithelial tissues [34]. Interestingly, the string-like cooperative motion of particles in a closeto glassy state were observed in super-cooled liquids [57,58], simulations of Lennart-Jones mixtures [59] and granular beads [60].…”
Section: Dynamic Heterogeneity Due To the Co-existence Of Locally Ent...supporting
confidence: 65%
“…This view is recently justified in ref . using the microscopic data from nuclear γ-resonance time-domain-interferometry experiments. …”
Section: Resultsmentioning
confidence: 99%
“…Another example indicating the imperative importance of the length scale dependence study is the reported crossover from microscopic dynamics dominated by the slow α-relaxation, to the Johari-Goldstein (JG) β-relaxation at a certain length scale as the temperature is decreased in the intermediate supercooled liquid region. Via neutron spin-echo (NSE) 18 20 and nuclear resonance X-ray scattering (NRXS) 21 23 , this slow α and JG β crossover which occurrs in the time scale of ≈10 ns to ≈10 3 ns has been directly observed, and its occurrence has been found to be wavevector ( Q )-dependent. This crossover occurs in the Q -range of the first minimum above the primary peak of the structure factor S ( Q ), but around the primary peak it is either not observed 21 , 22 or is too weak to be appreciated 23 , due to the local length scale of the JG β-process.…”
Section: Introductionmentioning
confidence: 99%
“…Via neutron spin-echo (NSE) 18 20 and nuclear resonance X-ray scattering (NRXS) 21 23 , this slow α and JG β crossover which occurrs in the time scale of ≈10 ns to ≈10 3 ns has been directly observed, and its occurrence has been found to be wavevector ( Q )-dependent. This crossover occurs in the Q -range of the first minimum above the primary peak of the structure factor S ( Q ), but around the primary peak it is either not observed 21 , 22 or is too weak to be appreciated 23 , due to the local length scale of the JG β-process. The technique of NSE, which encodes the dynamic signal in the spin of the neutrons and measures the Q -dependent intermediate scattering function (ISF) directly in time domain, offers the highest energy resolution among all neutron spectroscopy techniques and thus has been extensively employed for studying the relaxation dynamics of a wide variety of materials on the pico- to nanosecond time scale 19 , 24 36 .…”
Section: Introductionmentioning
confidence: 99%